Odpowiedzi

2010-02-15T16:42:40+01:00
A)6(x-4)
6x-24
6x=24/:6
x=4

b)2(x+1)-3(x-1)
2x+2-3x+3
-x=-5/:(-1)
x+5

c)-3(y-2)+4(y+2)
-3y+6+4y+8
y+-14
2010-02-15T16:46:26+01:00
A)6(x-4)=6x-24
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)jedna druga(4x-4)-2x=2x-2-2x=2
g)x(x-1)-3(x do kwadratu-x)=x²-x-3x²+3x=-2x²+2x
h)5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
i)3x(x+ jedna trzecia y)-2y(jedna drugax-jedna druga)=3x²+xy-xy+y=3x²+y
2010-02-15T16:49:26+01:00
A) 6(x-4)= 6x-24

b) 2(x+1)-3(x-1)= 2x+2-3x+3 = -x+5

c) -3(y-2)+4(y+2)= -3y + 6 + 4y +8= y+14

d) 5(x-y-1)-4(x+2) = 5x- 5y -5 -4x -8= x -5y -13

e) 2(3a+b)-2(a-b)= 6a+2b-2a+2b= 4a+4b

f) jedna druga(4x-4)-2x = 2x-2-2x= -2

g) x(x-1)-3(x do kwadratu-x)= x²-x-3x²+3x= -2x²+2x

h) 5a(a-3)-3a(a-5)= 5a²-15a-3a²+15a= 2a²

i) 3x(x+ jedna trzecia y)-2y(jedna drugax-jedna druga)= 3x²+xy-xy+y= 3x²+y